Enhancing diabetic care in the community in Malaysia: need for a paradigm shift - Gyanchand Rampal, Lekhraj Rampal; Loong, Yik Yee; Md Zain, Azhar; Lekhraj Rampal, Sanjay Rampal (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Efforts towards improving the management of diabetes mellitus has grown and progressed. Clinical studies and new drug discoveries have led to better treatment for patients. Most healthcare budgets devote an enormous amount of expenditure for the treatment of diabetes. However, despite all these efforts, the disease continues to grow and has been predicted to be unmanageable in the near future. Thus, there is a dire need to relook the current approaches and policies. “Prevention is better than cure” is definitely the precise solution to this catastrophe. A paradigm shift in strategies for the prevention of diabetes and treatment of its risk factors is an imperative.